KAJIAN SOSIAL EKONOMI PELAKSANAAN INSEMINASI BUATAN SAPI POTONG DI KABUPATEN KEBUMEN - Dewi Hastuti Hastuti; Sudi Nurtini; Rini Widiati (Universitas Wahid Hasyim, 2008)
This study was conducted to determine social-economic characteristics of farmers and inseminators, to determine the performance of beef cattle reproduction in the implementation artificial insemination (AI) program, institution of AI and to determine of income from beef cattle farmers was used AI and also factors influencing them. Respondents consist of 60 farmers and 33 Inseminators were taken by using purposive sampling. This research used primary data and secondary data were taken by using survey method. Observed variables were social-economic characteristic of respondent, performance of beef cattle reproduction (calf weaning, postpartum mating, service per conception (S/C) and calving interval (C.I)), institute of AI and income of beef cattle farmers. This research use analysis which consist of t- test to compare performance of beef cattle reproduction between AI program with natural breeding and regression analysis to know the factors affecting of income level. The result of research showed that calf weaning and C.I of AI at t- test have significant difference compare to natural breeding, post partum mating and S/C on AI and natural breeding shows insignificant difference. Analysis result of regression showed F equal to 9.007 significant (P< 0.01) and coefficient of determinant R2 equal to this 0.505 that mean 50.50% dependent variable can be explained by free variable, while the rest 49.50% explained by other variables outside. The factors that significantly affected the option of income are farm experience (P<0.01), cost of breeding (P<0.10), and dummy variable (P<0.01). The farm experience and dummy variable had positive effect while cost of breeding had negative effect. Keyword : Insemination, Beef cattle, Performance of reproduction.